Do we want children? Attitudes towards having or not having children: a comparative perspective on Spain and Poland - Juszczyk-Frelkiewicz, Katarzyna; Simó Solsona, Montserrat; López Villanueva, Cristina (Adult Education Discourses, 2022)
The transformations inherent to the Second Demographic Transition have evolved in intensity and timing in a differential manner in many European countries. The changes in demographic patterns are a reflection, to a large extent, of the transformations in values and attitudes towards fertility, nuptiality and forms of coexistence; transformations that act on a differential cultural, economic and political substratum in each national or regional context. Spain and Poland are two countries that have followed different processes; however, they are joined by a legal constraint, late chronology and economic recession. The aim of this paper is to analyse differences in attitudes of Spanish and Polish respondents towards having or not having children and the differences in two periods of time in both countries. In the article, fertility patterns in Poland and Spain were compared and examined in a dual perspective: firstly, considering the fertility data provided by official statistics. Secondly, from a subjective perspective considering attitudes and opinions about having or not having children. The Second Demographic Transition (SDT) is the theoretical background regarded as a driving force to understand this phenomenon. A subjective perspective on fertility was analysed on the data from the European Social Survey (ESS) in two periods of time: during rounds three (2006) and nine (2018), to capture the changes in respondents’ attitudes to having or not having children. Independent samples of tests and ananalysis of variance (ANOVA) were used in statistical analyses and were performed using SPSS. The results reflect differences in both countries. While Spain began a change in attitudes towards parenthood (having or not having children) in the early 1980s, and during the analysed period was consolidating its opinion, the starting point from Poland is more conservative, but shows an intense move towards being more flexible with new behaviour patterns.